COVID-19 Vaccination Status and Pregnancy Outcome during Third Wave - Dey, Madhusudan; Tiwari, Shyamji; Chawla, Sunil; Dhume, Pranjali; Kumar, Abhijit; Chowdhary, Priyanshi; Rawal, Reshu (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: Omicron was declared as a variant of concern by WHO on 26 Nov 2021. Omicron is highly transmissible, but the disease severity and morbidity were lesser compared to the Delta variant. However, COVID-19 Vaccine efficacy was reduced for the Omicron variant whereas it was highly efficacious for the Delta variant. Hence, for evidence-based counseling in pregnant patients about expected outcomes depending on their vaccination status, this prospective cohort study was conducted. STUDY DESIGN: This study was conducted in Base Hospital Delhi Cantt, New Delhi, India during the third wave of SARS-CoV-2 i.e. from Jan 2022 to Mar 2022. All COVID-19-positive patients who were admitted for delivery were followed up till discharge from the hospital. The outcomes in terms of severity of COVID-19 infection, period of gestation at the time of delivery, intrapartum/postpartum complications, fetal distress, meconium staining of liquor, the requirement of neonatal intensive care unit admission were documented and data was analyzed to assess clinical severity of the disease in fully/partially vaccinated+unvaccinated women. RESULTS: During the specified period, 22.32% was the positivity rate among the delivered patients. Of 61.78% were fully vaccinated and 24.39% were either not vaccinated or partially vaccinated. The risk of symptomatic COVID-19 illness, the requirement of supportive management, and maternal and neonatal outcomes in both groups were comparable. CONCLUSION: Unvaccinated or partially vaccinated parturient had no increased risk of symptomatic COVID-19 illness or requirement of supportive management in terms of oxygen inhalation or ventilation as compared with fully vaccinated pregnant women. The study also reported comparable maternal and fetal outcomes in vaccinated and unvaccinated/ partially vaccinated pregnant women. Further studies are required to ascertain whether the comparable outcomes were due to the decreased severity of the disease caused by the omicron variant.